Mild External Compression of the Leg Increases Skin and Muscle Microvascular Blood Flow and Muscle Oxygenation during Simulated Venous Hypertension - Macias, B. R.; Neuschwander, T. B.; Hargens, A. R.; Zhang, Q. (ISRN vascular medicine, 2012)
We studied the effect of mild external leg compression on both skin and muscle microvascular flow, and muscle oxygenation in the leg of healthy subjects during simulated venous hypertension. Skin and muscle microvascular blood flows were measured using photoplethysmography (PPG), and muscle oxygenation was measured using near-infrared spectroscopy (NIRS). Both PPG and NIRS probes were placed over the anterior compartment of the right leg in 8 healthy subjects. Measurements were taken under three experimental conditions: external leg compression (40 mmHg); simulated venous hypertension (65 mmHg thigh cuff); external leg compression during simulated venous hypertension. Muscle oxygenation was measured only under external leg compression during simulated venous hypertension. Simulated venous hypertension decreased skin and muscle microvascular blood flows from 100% (baseline) to 35.8±2.9% and 31.9±1.3% (P<0.001), respectively. External leg compression during simulated venous hypertension caused 2-fold increases in both skin and muscle microvascular blood flows compared to simulated venous hypertension (P<0.001). Similarly, external leg compression during simulated venous hypertension significantly restored muscle oxygenation by 23±7% compared to its baseline (P<0.05). Our results demonstrate that mild external leg compression counteracts the decreases in skin microvascular flow, muscle microvascular flow, and muscle oxygenation induced by simulated venous hypertension in the leg.